Thyroid Ultrasound Pitfalls: Esophageal Fibrovascular Polyp Mimicking Thyroid Nodule - Anna Ansaloni; G. Brigante; B. Madeo (Case Reports in Endocrinology)
Background. Ultrasound (US) is the most accurate tool in the diagnosis of thyroid nodules if performed by expert physician. Misdiagnosis due to extrathyroidal lesions mimicking thyroid nodules is reported in literature. We describe the first case of an esophageal fibrovascular polyp misdiagnosed as a thyroid nodule on US examination. Patient Findings. A 54-year-old woman presented to emergency department for headache and underwent carotid Doppler extended to neck ultrasound with incidental finding of a nodule in the posterior side of the left thyroid lobe. A following thyroid US performed by an endocrinologist allowed the characterization of the lesion as an esophageal pathology, considering the extrathyroidal position, the typical peripheral hyperechoic spots and hypoechoic rim, the connection to the esophagus, and the swallowing connected movement. The patient was addressed to further investigations and finally to anterior pharyngotomy with histological diagnosis of esophageal fibrovascular polyp. Summary. Differential diagnosis between thyroid nodules and other neck lesions is important to prevent an unnecessary fine needle aspiration biopsy and to treat the extrathyroidal pathology. In this case, an US performed by an expert endocrinologist allowed detecting an esophageal fibrovascular polyp requiring surgical removal. In conclusion, the possibility of an esophageal pathology, and even fibrovascular polyp, should be considered during US thyroid examination.